Genetically based resistance to summer mortality in the Pacific oyster (Crassostrea gigas) and its relationship with physiological, immunological characteristics and infection processes - Samain, Jean-François; Degremont, Lionel; Soletchnik, Patrick; Haure, Joel; Bédier, Edouard; Ropert, Michel; Moal, Jeanne; Huvet, Arnaud; Bacca, Hélène; van Wormhoudt, Alain; Delaporte, Maryse; Costil, K.; et al. (Aquaculture, 2007)
International audience Summer mortality of Pacific oysters is known in several countries. However no specific pathogen has been systematically associated with this phenomenon. A complex combination of environmental and biological parameters has been suggested as the cause and is now starting to be identified. A high genetic basis was found for survival in oysters when a first generation (G1) was tested in three sites during summer. This paper presents a synthesis on physiological characteristics of two selected groups (‘R' and ‘S', from families selected for resistance and susceptibility to summer mortality respectively), of the second and third generations. R and S showed improvement or reduction of survival compared with the control in both field and laboratory trials confirming the high heritability of survival of juveniles <1 year old. Interestingly, no correlation was observed between growth and survival. Comparison between the two selected groups showed that S oysters invested more energy in reproduction and stayed a longer time without spawning than R oysters which had high synchronous spawning. This was mainly shown with high rather than low dietary rations (respectively 12% and 4% DW algae/DW oyster) in a controlled experiment. Moreover, early partial spawning was detected in S oysters and not R ones in the high dietary ration. S showed a higher respiration rate and an earlier decrease in absorption efficiency than R during gametogenesis, but they were not significantly different in glycogen or ATP utilisation. Two months before a mortality episode, hemocytes from S oysters had a higher adhesive capacity than R hemocytes and significantly higher reactive oxygen species production capacity. One month before mortality, S oysters had the highest hyalinocyte concentration and their expression of genes coding for glucose metabolism enzymes (Hexokinase, GS, PGM, PEPCK) was significantly lower in the labial palps. After a thermal increase from 13 °C to 19 °C, during 8 days in normoxia, S oysters showed a ...